Variability of secondary metabolites from leaves of Ziziphus mauritiana obtained from different locations in Sumbawa, Indonesia - IHLANA NAIRFANA; ALUH NIKMATULLAH; MUHAMMAD SARJAN; ADNAN TANDEANG (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Nairfana I, Nikmatullah A, Sarjan M, Tandeang A. 2022. Variability of secondary metabolites from leaves of Ziziphus mauritiana obtained from different locations in Sumbawa, Indonesia. Biodiversitas 23: 4948-4958. Bidara (Ziziphus mauritiana L.) is an evergreen shrub that grows in many parts of the world, and is an important plant in arid and semi-arid regions for the environment, food, and health. The plant has been used traditionally as medicine, and more recently, growing scientific evidence demonstrated the active compounds of bidara leaves. However, little is known about the plant's secondary metabolite profiles in different environments. This research aimed to characterize the secondary metabolites profile of bidara leaf obtained from the different habitats of semi-arid Sumbawa Island, Indonesia, and to evaluate their relationship based on cluster analysis of the secondary metabolite diversity. The leaf samples were collected from bidara plants obtained in 3 districts on Sumbawa Island: West Sumbawa (SB), Sumbawa (KS), and Dompu (DP) Districts, each from different ecosystems: lowland coastal/savanna, lowland near residential areas, and mid-highland areas of residential or forest-edge. The leaf samples were extracted by maceration with multilevel extraction using solvents with decreased polarity (h-hexane, ethyl acetate, ethanol 70%, methanol, and distilled water, respectively), followed by phytochemical screening for the presence of alkaloid, flavonoid, saponin, and phenolic. The results showed variation in the phytochemical components of bidara leaves obtained from a different environment, with secondary metabolites of DP leaves being more diverse than KS and other SB. All samples contained polar alkaloids and flavonoids, while the DP1 samples also contained non-polar flavonoids. The SB1 and DP samples also contained saponin. Interestingly, phenolic was only detected in the polar extracts of DP1 leaves. Cluster analysis based on the secondary metabolites profile distinguished the SB1 and DP1 bidara from others. Further study is required to understand if the variation is resulted from bidara adaptation to a different environment or also due to genetic variation of the bidara in Sumbawa Island.